Analisis efisiensi modal kerja koperasi pegawai republik indonesia gotong royong kecamatan klego kabupaten boyolali - Saputro, Eko, Drs. Agus Muqorrobin, M.M (2015)
This study aims to determine whether the financial condition of the District Mutual Cooperation KPRI Klego Boyolali already profitable in terms of liquidity, activity and profitability. This study is to analyze the financial statements at KPRI Mutual Cooperation which includes balance sheet and income statement. The data used is secondary data. Analysis tools used are: (1) Analysis of liquidity, measured by the current ratio, cash ratio and quick ratio; (2) Analysis of activity, measured by the turnover of cash, accounts receivable and working capital; (3) Analysis of profitability, measured by profitability. Based on the results of data analysis, we concluded that: (1) In terms of liquidity ratios such as current ratio and cash ratio in the year 2010 to 2014 indicate that the financial condition of KPRI Mutual Cooperation is very good, particularly in meeting the obligation or short-term debt. From the analysis it can be concluded that the liquidity ratio KPRI Mutual Cooperation Klego District of Boyolali District has been efficient in the use of capital. (2) Judging from the activity ratio, the level of Mutual Cooperation KPRI cash turnover is relatively high with the average value of the cash turnover of 593.12 times or have the time rotating for 0.6 days (1 day). KPRI receivable turnover rate of Mutual Cooperation is fairly low at an average of 0.28 times or have time bound for 1268 days (3.5 years) .. working capital turnover rate is relatively low KPRI Mutual Cooperation, which is an average working capital turnover of 0.36 times. Thus it can be stated that the management of working capital by KPRI Mutual Cooperation less efficient. (3) In terms of profitability ratios such as Return on Working Capital in 2010 to 2014 indicate that the financial condition of Mutual Cooperation KPRI is unfavorable. This shows that KPRI Mutual Cooperation has not been efficient in the use of working capital to make a profit.